1985
DOI: 10.1099/00221287-131-6-1393
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in a Microbial Fuel Cell. Stoichiometry of Product Formation in a Thionine-mediated Proteus vulgaris Fuel Cell and its Relation to Coulombic Yields

Abstract: The pattern of glucose metabolism was studied in a thionine-mediated Proteus culgaris fuel cell by using lT-labelled glucose. Added glucose was rapidly taken up by the bacteria and converted to CO', acetate, lactate and a fourth product, tentatively identified as propionate. When the glucose-dependent electric current from the fuel cells had been completely discharged, about 50% of glucose carbon was found in C 0 2 , 30% in acetate, 10% incorporated in the bacteria, and the residual 10% distributed as small am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 5 publications
3
27
0
1
Order By: Relevance
“…Previous investigations (2,20) have shown that in microbial fuel cells in which thionin is the electron mediator, the levels of both current and potential decrease when the resting cells are depleted of glucose (i.e., fuel). We performed fuel cell experiments with NR to determine the maximal electrical productivities and stabilities that could be generated by E. coli resting cells in the presence of different glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations (2,20) have shown that in microbial fuel cells in which thionin is the electron mediator, the levels of both current and potential decrease when the resting cells are depleted of glucose (i.e., fuel). We performed fuel cell experiments with NR to determine the maximal electrical productivities and stabilities that could be generated by E. coli resting cells in the presence of different glucose concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies (2,5,7,16,20) of microbial fuel cells the workers did not examine the impact of NADH oxidation via generation of electricity on cellular physiology (i.e., the impact on growth and end product formation). In resting cell studies it was assumed that generation of electricity as a consequence of NADH oxidation would result in lower levels of reduced metabolic products and higher levels of oxidized products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modelling study is based on the detailed experimental observations by Bennetto's group in the 1980s [5,21,24] and Kim's work in the late 1990s [11]. For convenience, their experimental setup is briefly described here.…”
Section: Methodsmentioning
confidence: 99%
“…In this model we describe in detail only the dynamic behaviour of the anodic compartment, having in mind that a description of the cathodic chamber can follow the same approach. The model will be used to interpret experimental data obtained by Bennetto's group on MFCs with added soluble mediator (thionine) and suspended Proteus cells [5,21,24]. Such a model is also useful because it points to parameters that still need to be measured.…”
Section: Introductionmentioning
confidence: 99%